Conflicting roles for a cell surface modification in Salmonella. Issue 5 (5th May 2013) - May, John F.; Groisman, Eduardo A.
Summary Chemical modifications of components of the bacterial cell envelope can enhance resistance to antimicrobial agents. Why then are such modifications produced only under specific conditions? Here, we address this question by examining the role of regulated variations in O‐antigen length in the lipopolysaccharide (LPS), a glycolipid that forms most of the outer leaflet of the outer membrane in Gram‐negative bacteria. We determined that activation of the PmrA/PmrB two‐component system, which is the major regulator of LPS alterations in Salmonella enterica serovar Typhimurium, impaired growth of Salmonella in bile. This growth defect required the PmrA‐activated gene wzzst, which encodes the protein that determines long O‐antigen chain length and confers resistance to complement‐mediated killing. By contrast, this growth defect did not require the wzzfepE gene, which controls production of very long O‐antigen, or other PmrA‐activated genes that mediate modifications of lipid A or core regions of the LPS. Additionally, we establish that long O‐antigen inhibits growth in bile only in the presence of enterobacterial common antigen, an outer‐membrane glycolipid that contributes to bile resistance. Our results suggest that Salmonella regulates the proportion of long O‐antigen in its LPS to respond to the different conditions it faces during infection.